When only China wants to play: Institutional turmoil and Chinese investment in Brazil - Søndergaard,Niels (2022)
Abstract The political and institutional crisis in Brazil from 2015, fueled largely by corruption probes and lawfare, had severe repercussions within the Brazilian construction and energy sectors. While many international investors withdrew from Brazil in this period, Chinese investment surged. This article accounts for the particular characteristics of Chinese investments, such as sectorial complementarities, risk assessment, market size attraction, and state-drivenness, which may explain this development.